Geophysical investigations of the Powell Basin bottom structures (West Antarctica) - V. D. Solovyov; I. N. Korchagin; V. M. Vaschenko (Ukrainian Antarctic Journal, 2008)
Magnetic anomalies obtained during Ukrainian Antarctic expeditions show large amplitude in the northern margin of the Powell Basin. These anomalies are attributed to the continuation of the branches of the Antarctic Peninsula Pacific Margin Anomaly. Different variants of connection between this anomaly and the anomalies in the Powell Basin are discussed. It may be the variant with the occurrence of two branches. One of them lies along the South Scotia Ridge whereas the second, more southern branch, may be located in the eastern and western passive margins of the Powell Basin. The upper surface of magnetic bodies is consistent with anomaly horizon at depth of 3-18km that was obtained from the modelling of deep crust structure by VERS method.